Implementation of School Information System at Yaabunaya Fathul Khair Makassar Foundation - Kamaruddin; Mustika, Nur; Emasari; Taliang, Askar; Wisda; Amiruddin, Erwin Gatot (Ceddi Journal of Education, 2022)
This research aims to evaluate the implementation of a school information system at the Yaabunaya Fathul Khair Foundation in Makassar and its impact on school management processes. The system is designed to enhance interaction between the school and various stakeholders while ensuring the generation of accurate information. The analysis employs the PIECES method, which examines Performance, Information, Economics, Control, Efficiency, and Service to identify and address issues within the foundation. The research utilizes UML for design, PHP for coding, and MySQL for database management. System testing was conducted using the Black Box method to verify functional performance. The results indicate that the developed system operates effectively and meets its intended functions. User feedback gathered from a questionnaire with 6 respondents answering 10 questions, revealed an average satisfaction score of 86.79%, demonstrating that the application performs well and meets user expectations. This research contributes to the field of educational technology by providing insights into the effective implementation and evaluation of school information systems, highlighting their role in improving school management and stakeholder communication.